2008
DOI: 10.1002/gps.1992
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia––a clinically complex diagnosis

Abstract: More knowledge about early presenting cognitive and behavioural signs of FTD is needed in both primary and secondary health care to reduce the time period needed to establish a clinical diagnosis of FTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
2
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 21 publications
5
66
2
8
Order By: Relevance
“…Although the findings regarding time to diagnosis in YOD patients are supported by the previous literature, this period was much longer than that previously found : 3.3 years in the YO-AD group, 4.9 years in the YO-FTD group and 1 year in the LOD group (Wilkinson et al 2004 ;Rosness et al 2008). This discrepancy could be a result of country-related differences or differences in the way the time between symptom onset and diagnosis was estimated.…”
Section: The Age At Onset Effectcontrasting
confidence: 80%
“…Although the findings regarding time to diagnosis in YOD patients are supported by the previous literature, this period was much longer than that previously found : 3.3 years in the YO-AD group, 4.9 years in the YO-FTD group and 1 year in the LOD group (Wilkinson et al 2004 ;Rosness et al 2008). This discrepancy could be a result of country-related differences or differences in the way the time between symptom onset and diagnosis was estimated.…”
Section: The Age At Onset Effectcontrasting
confidence: 80%
“…The identification of early prodromal states in FTD continues to pose challenges [54]. Studies have found that it can take from 5 to 10 years to make a correct diagnosis [55, 56], and our findings warrant more research to further explain the correlation between anxiety and FTD.…”
Section: Discussionmentioning
confidence: 99%
“…It is different from Alzheimer's dementia manifested by impaired executive functioning and progressive semantic or non-fluent aphasia which eventually leads to mutism. [22][23][24][25][26] Recent work has shown that ALS and FTD are both associated with aggregation of ubiquitin-positive inclusion bodies that are positive for the TAR-DNA binding protein TDP-43 (encoded by TARDBP). A number of different mutations in TDP-43 are being discovered.…”
Section: The Clinical Spectrummentioning
confidence: 99%